(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Now a days ICT has become the backbone of all communication system. Its ranges from education to business, research to industry, health care to automation. The wide coverage and the reliable bandwidth[29] offered by the broadband satellite systems has made them a promising media for IP streaming. But the demand for exploring new solutions concerning this industry has kept increasing to maintain the growth rate require by the various market sectors.